2019
DOI: 10.1016/j.scitotenv.2019.06.121
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of spray drift potential reduction for hollow-cone nozzles: Part 1. Classification using indirect methods

Abstract: Està subjecte a una llicència de Reconeixement-NoComercial-SenseObraDerivada 3.0 de Creative Commons

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 28 publications
(29 reference statements)
0
16
0
Order By: Relevance
“…The LiDAR results were also compared with those obtained in wind tunnel tests carried out by Torrent et al (2019). Fig.…”
Section: Comparison Between Lidar and Indirect Methodsmentioning
confidence: 99%
“…The LiDAR results were also compared with those obtained in wind tunnel tests carried out by Torrent et al (2019). Fig.…”
Section: Comparison Between Lidar and Indirect Methodsmentioning
confidence: 99%
“…Researchers have adopted different techniques using the influencing factors to study how to reduce spray drift 24–28 . For many years, efforts to reduce spray drift focused on producing larger droplets 15 .…”
Section: Introductionmentioning
confidence: 99%
“…23 Researchers have adopted different techniques using the influencing factors to study how to reduce spray drift. [24][25][26][27][28] For many years, efforts to reduce spray drift focused on producing larger droplets. 15 Nozzle type 13 and nozzle size 29 have the greatest influence on droplet size and velocity.…”
Section: Introductionmentioning
confidence: 99%
“…The suggested threshold nozzles for these drift reduction classes in orchard spraying are, respectively: TeeJet DG8002 (drift reduction of 62%), Albuz AVI 80015 (drift reduction of 74%), and Albuz TVI 80025 (drift reduction of 97%), all at 7-bar spray pressure, as well as Lechler ID 9001 (drift reduction of 91%) at 5-bar pressure. Another study revealed that the V100 achieved a high correlation (up to R 2 = 0.948) with the drift potential tested with the wind tunnel for hollow-cone nozzles [ 148 ].…”
Section: Other Factors Affecting Performance In Sprayingmentioning
confidence: 99%